The effects of two combined methods of P53 expression and preoperative serum CEA detection on the prognosis of colorectal cancer - Guojun Tong; Guojun Tong; Yanyan Wang; Hai Qian; Zhenhua Tan; Yan Shen; Hui Li (Frontiers in Oncology)
AimTo explore the effects of two combined methods—P53 expression and preoperative serum carcinoembryonic antigen (S-CEA) detection—on the prognosis of colorectal cancer (CRC).MethodsTwo classified combinations of tissue P53 and S-CEA were utilized: Combined P53 groups (normal P53 and S-CEA, or one or both elevated) and Recombined groups (P53 normal & S-CEA normal, P53 normal & S-CEA high, P53 high & S-CEA normal, P53 high & S-CEA high). Clinicopathologic features were analyzed by P53, S-CEA, Combined P53, and Recombined P53. Correlations between them were examined. Overall survival (OS) and disease-free survival (DFS) were evaluated using the Kaplan-Meier method and Log-Rank test. Univariate and multivariate analyses were performed for Combined P53 and Recombined P53 to determine independent factors. Three-year, two-year, and one-year OS and DFS were further analyzed using multimeROC. SPSS 27 and R 4.4.1 were used for analysis.ResultsTNM stage, CA199, differentiation, tumor maximum size, and minimum size showed significant differences between the single P53 and S-CEA groups (all P < 0.05). TNM stage, CA199, and chemotherapy differed in both Combined P53 and Recombined P53 groups (all P < 0.05). Significant correlations were found between P53, S-CEA, Combined P53, and Recombined P53 (all P < 0.001). No significant differences in OS and DFS were observed with P53 and Combined P53 (all P > 0.05), but differences were noted with S-CEA and Recombined P53 (all P < 0.05). Univariate and multivariate analyses identified laparoscopy, chemotherapy, differentiation, TNM stage, and Recombined P53 as independent factors for OS and DFS, while P53, S-CEA, and Combined P53 were not. Further multimeROC analysis showed that 3-year OS had better sensitivity and specificity (Area Under Curve [AUC] = 0.54), and 1-year DFS was better (AUC = 0.59).ConclusionsRecombined P53 classification was more effective than traditional Combined P53 classification for assessing CRC prognosis and was an independent factor. Additionally, the 3-year OS and 1-year DFS analysis demonstrated higher sensitivity and specificity with Recombined P53.